Hubungan Antara Perilaku Makan Dan Body Image Dengan Status Gizi Mahasiswa Putri Keperawatan Universitas Putra Abadi Langkat - Srinur Nilawati (Universitas Pahlawan Tuanku Tambusai, 2023)
Dissatisfaction with body shape very often we meet in young women. This dissatisfaction made the young women apply improper behavior in achieving the ideal body by doing a diet that is too strict, that will have a negative impact on nutritional status. This research was conducted to analyze the relationship between eating behavior and body image with the nutritional status of female nursing students. This research is an observational study with a cross sectional design on 72 female nursing students at Faculty of Health Science, Putra Abadi Langkat University. Sample selection using simple random sampling that meets the inclusion criteria. Body image data and eating behavior were obtained using a questionnaire. Data on nutritional status were obtained from measurements of height and weight, then the z-score was calculated based on BMI/U. Based on the results of the analysis, it was found that 41 respondents (56.9%) had not practiced good eating habits and 31 respondents (43.1%) had practiced good eating habits. Meanwhile, 29 respondents (40.3%) were dissatisfied with their body shape and 43 respondents (59.7%) were satisfied with their body shape. There is a significant relationship between eating behavior and nutritional status (r=0.507 p-0.001) and body image and nutritional status (r=0.482 p=0.001). The conclusion from this study is that there is a significant relationship between eating behavior and body image with the nutritional status of female nursing students at Faculty of Health Science, Putra Abadi Langkat University. Keywords: eating behaviour, body image, nutritional status